Application of a Relative Visual Performance Model in a Virtual Reality Immersive System - Perroud, Benoit; Regnier, Stephane; Kemeny, Andras; Merienne, Frederic (IEEE transactions on visualization and computer graphics, 2020)
As part of an evaluation process of user experience realism in a Virtual Reality (VR) system, we focus in this paper on one of the core characteristics of vision: the relationship between contrast and luminance. The experiment aims at validating in VR reaction time predictions given by Rea and Ouellette's model. The subjects have to distinguish, as fast as they can, a target object from an uniform background. Our results did not match the predictions of the model. Our subjects showed higher performance in performing the task than expected. At low level of contrast, our subjects could easily perceive a target they should not have been able to see at all. This is explained by the size of the visual field surrounding the target: at low level of visibility, the larger the surrounding, the easier perception the is. We conclude that the Rea and Ouellette's model could be applied in VR if a specific visual field size factor was added.